Rethinking the financial Kuznets curve in the framework of income inequality: Empirical evidence on advanced and developing economies - Özdemir, Onur (Economics and Business Letters, 2019)
Contrary to the empirical findings that there is a negative link between financial sector development and income inequality, we introduce a different result: in the earlier stages of the financial and economic development, the level of income inequality decreases, but with an ongoing developmental process, the later stages show that the above-mentioned link between finance and inequality turns into positive within the framework of financial Kuznets curve. In terms of finance-inequality nexus, we find that neither markets nor institutions play a significant role for the decrease in income inequality. When the results are measured within this context, the study concludes that the U-shaped financial Kuznets curve hypothesis is valid in the sample countries.